Efektivitas Pembelajaran Bahasa Inggris Berbasis Case Method dalam Meningkatkan Keterampilan Negosiasi Bisnis Mahasiswa Manajemen - Hajarudin Hajarudin (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study investigates the effectiveness of the case method in enhancing business negotiation skills through English language learning among management students at STIE Ganesha. Employing a qualitative approach, data were gathered via in-depth interviews, participatory observations of cross-cultural negotiation simulations, and thematic analysis of reflection journals from 20 purposively selected participants. Findings revealed three core themes: (1) the case method deepened contextual understanding of business communication strategies through localized scenarios, such as partnerships with Balinese SMEs; (2) iterative case discussions enhanced adaptive problem-solving skills in multicultural settings; and (3) collaborative analysis strengthened persuasive language use and emotional intelligence. Key challenges included uneven group participation dynamics and balancing linguistic precision with strategic negotiation goals. The study proposes a pedagogical framework integrating localized case narratives (e.g., disputes over sacred land use or artisan collaborations) and structured peer feedback to align language education with managerial competencies. These insights underscore the role of situated learning in bridging theoretical knowledge and practical negotiation praxis within Bali’s unique global-local business ecosystem.